The Risk Components of Liquidity - Lorań Chollete; Randi Næs; Johannes A. Skjeltorp (Norges Bank, 2008)
Does liquidity risk differ depending on our choice of liquidity proxy? Unlike literature that considers common liquidity variation, we focus on identifying different components of liquidity, statistically and economically, using more than a decade of US transaction data. We identify three main statistical liquidity factors which are utilized in a linear asset pricing framework. We motivate a correspondence of the statistical factors to traditional dimensions of liquidity as well as the notion of order and trade based liquidity measures. We find evidence of multiple liquidity risk premia, but only a subset of the financial liquidity factors are associated with significant risk premia. These are the factors that we relate to the dimensions of immediacy and resilliency, while the depth dimension does not command a risk premium in any of the models. Our results suggests caution when choosing liquidity variables in asset pricing applications, since liquidity premia may be reflected in only some dimensions of liquidity.
hdl:11250/2497783
Keywords: G12; G14; 330; liquidity risk; liquidity factors; asset pricing; market microstructure